2016
DOI: 10.1186/s12993-016-0113-0
|View full text |Cite
|
Sign up to set email alerts
|

Association of tryptophan hydroxylase-2 polymorphisms with oppositional defiant disorder in a Chinese Han population

Abstract: Background: Oppositional defiant disorder (ODD) is a behavioral disorder of school-age population. It is well known that 5-HT dysfunction is correlated with impulsivity, which is one of the common characteristics of ODD. The enzyme tryptophan hydroxylase-2 (TPH-2) synthesizes 5-HT in serotonergic neurons of the midbrain raphe. The purposes of this study were to investigate the potential association of TPH-2 polymorphisms with susceptibility to ODD in a Han Chinese school population.Methods: Four polymorphisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…Serotonin (5-HT) is one of the most important neurotransmitters involved in many personal behaviors such as attention, community behavior, appetite, and activity. It has been shown that deficiency of this neurotransmitter or its dysfunction can lead to psychological disorders (26).…”
Section: Introductionmentioning
confidence: 99%
“…Serotonin (5-HT) is one of the most important neurotransmitters involved in many personal behaviors such as attention, community behavior, appetite, and activity. It has been shown that deficiency of this neurotransmitter or its dysfunction can lead to psychological disorders (26).…”
Section: Introductionmentioning
confidence: 99%
“…However, CU traits may be insufficient to produce aggression, and complex corroborating processes linked to aggression may need to be present for this pathway to operate. Finally, the relatively recent discovery of TPH‐2, with a more central role in CNS 5‐HT synthesis than TPH‐1, has been detected to be implicated in aggression‐related behaviours in animal studies and in human genetic designs , possibly via impacting 5‐HT synthesis in the orbitofrontal cortex . Animal studies have found that brain 5‐HT plays a paradoxical role in bone mass – previously thought to be exclusively a function of peripheral 5‐HT .…”
Section: Discussionmentioning
confidence: 99%
“…The imbalance of excitatory serotonin function has also been related to ADHD development [ 89 , 90 ]. Serotonin dysfunction plays a mediator role in ADHD-related hyperactive and impulsive behaviours [ 91 ] inducing impaired control of impulses, violent behaviour, concentration and appetite [ 89 ]. Moreover, serotonin regulates DA activity through its receptors 5-hydroxytryptamine receptor 1B (5-HTR1B) or 5-hydroxytryptamine receptor 2A (5-HTR2A).…”
Section: Adhd Aetiology and Pathophysiologymentioning
confidence: 99%